PO29 | Quality of anticoagulation as a predictor of early left ventricular thrombosis resolution: a retrospective cohort study (Bleeding, Thrombosis and Vascular Biology, 2025)
Introduction: International guidelines on management of left ventricular thrombosis (LVT) recommend oral anticoagulant therapy with vitamin K antagonists (VKAs) for at least 3 to 6 months. VKAs seemed to afford for a high rate of thrombus resolution, a low rate of stroke and of bleeding events. Maintaining a good quality of VKAs therapy is, therefore, mandatory to achieve these outcomes. The most used tool in clinical practice to evaluate the quality of anticoagulation is the time in therapeutic range (TTR). The International Normalized Ratio (INR) variability is rarely used and its ability to predict patients’ outcomes is poorly defined. The objective of this study was to evaluate the association between the quality of anticoagulant therapy and early LVT resolution.